2014
DOI: 10.1037/a0035670
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal test of a developmental model of the transition to early drinking.

Abstract: This paper reports on a longitudinal test of a developmental model of early drinking that specifies transactions among personality, learning and behavior in the risk process. The model was tested on 1906 children making the transition from elementary school to middle school across three time points: the spring of 5th grade, the fall of 6th grade, and the spring of 6th grade. In a transaction that has been referred to as Acquired Preparedness, individual differences in the trait positive urgency at the end of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(95 citation statements)
references
References 88 publications
3
88
0
4
Order By: Relevance
“…Evidence from the present study supports the occurrence of a critical developmental period for positive alcohol expectancies, an illustration of the extent of growth that occurs, and the time at which the greatest growth is likely to occur. These fi ndings are consistent with those of Settles et al (2014), in which the transition from fi fth to sixth grade was associated with increases in positive alcohol expectancies for social facilitation, which subsequently predicted drinking at the end of sixth grade. Given our knowledge of how positive alcohol expectancies are associated with increased use of alcohol, the next logical step is to conduct research to discover how, when, and under what conditions negative alcohol-outcome expectancies develop and how this knowledge can best be incorporated into programs for prevention of problem drinking and alcohol abuse/dependence.…”
Section: Discussionsupporting
confidence: 80%
“…Evidence from the present study supports the occurrence of a critical developmental period for positive alcohol expectancies, an illustration of the extent of growth that occurs, and the time at which the greatest growth is likely to occur. These fi ndings are consistent with those of Settles et al (2014), in which the transition from fi fth to sixth grade was associated with increases in positive alcohol expectancies for social facilitation, which subsequently predicted drinking at the end of sixth grade. Given our knowledge of how positive alcohol expectancies are associated with increased use of alcohol, the next logical step is to conduct research to discover how, when, and under what conditions negative alcohol-outcome expectancies develop and how this knowledge can best be incorporated into programs for prevention of problem drinking and alcohol abuse/dependence.…”
Section: Discussionsupporting
confidence: 80%
“…Concurrently, there has also been extensive interest in documenting the development and potential co-development of traits related to sensation seeking and “impulsivity” during adolescence across various research domains (e.g., Burt, Sweeten, & Simons, 2014; Collado, Felton, Macpherson, & Lejuez, 2014; Harden & Tucker-Drob, 2011; Pedersen, Molina, Belendiuk, & Donovan, 2012; Quinn & Harden, 2013; Romer, 2010; Romer & Hennessy, 2007; Shulman, Harden, Chein, & Steinberg, 2014; Settles, Zapolski, & Smith, 2014; Steinberg et al, 2008). Neurodevelopmental changes evident during adolescence in both the prefrontal cortex and the limbic system appear to influence changes in phenomena related to impulsivity during adolescence (see Casey et al, 2010; Romer, 2010 for overviews).…”
Section: Introductionmentioning
confidence: 99%
“…Although traits related to urgency (both positive and negative) seem to be the most predictive of numerous risky behaviors (see Berg et al, in press) compared to other impulsivity facets, only one prospective study (to our knowledge) has examined the urgency measures during adolescence. Settles et al (2014) reported means of positive urgency, but these spanned a very short interval, from spring of 5th grade through spring of 6th grade.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, individuals are more likely to engage in drinking and driving if they perceive drinking and driving as less dangerous (Amlung et al, 2014;Bingham et al, 2007;Morris et al, 2014), believe that their peers are more accepting of drinking and driving (Bingham et al, 2007;LaBrie et al, 2012), or have higher perceived alcohol limits for driving safely (Gulliver & Begg, 2004;Royal, 2003). Theoretical models of risk behavior such as the Theory of Planned Behavior (Ajzen, 1991), and models specific to alcohol-related behaviors such as the Acquired Preparedness Model (Corbin et al, 2011;Settles et al, 2014), posit that these factors reflect a common pathway by which distal risk factors (e.g., impulsivity) converge to influence engagement in specific behaviors, including drinking and driving (LaBrie et al, 2012;Treloar et al, 2012). …”
Section: S Everal Individual Difference Factorsmentioning
confidence: 99%